2019
DOI: 10.21273/hortsci14021-19
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Phytophthora Crown Rot in Cucurbita pepo

Abstract: Phytophthora crown rot, caused by Phytophthora capsici Leonian, is a devastating disease in commercial squash (Cucurbita pepo L.) production across the United States. Current management practices rely heavily on the use of chemical fungicides, but existence of fungicide-resistant pathogen populations has rendered many chemicals ineffective. Host resistance is the best strategy for managing this disease; however, no commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…On the contrary, the Table Queen cultivar was highly susceptible as evidenced by a rapid expansion of water-soaked lesions to the cotyledons and subsequent wilting and death. The phenotypic distribution in the F 2:3 population was normal, but skewed towards susceptibility, thus supporting a three-gene model previously described for resistance in #181761-36P [15]. A similar skewed distribution was observed in a C. pepo F 2:3 population derived from a cross between a crown rot resistant breeding line #Pc-NY21 and a susceptible cultivar (#Dunja F 1 ) [10], indicating a similar but independent inheritance pattern in both resistant sources.…”
Section: Phenotypic Analysissupporting
confidence: 85%
See 2 more Smart Citations
“…On the contrary, the Table Queen cultivar was highly susceptible as evidenced by a rapid expansion of water-soaked lesions to the cotyledons and subsequent wilting and death. The phenotypic distribution in the F 2:3 population was normal, but skewed towards susceptibility, thus supporting a three-gene model previously described for resistance in #181761-36P [15]. A similar skewed distribution was observed in a C. pepo F 2:3 population derived from a cross between a crown rot resistant breeding line #Pc-NY21 and a susceptible cultivar (#Dunja F 1 ) [10], indicating a similar but independent inheritance pattern in both resistant sources.…”
Section: Phenotypic Analysissupporting
confidence: 85%
“…The high resistance to Phytophthora crown rot observed in #181761-36P confirms this accession as a good source for resistance breeding in C. pepo [14,15]. On the contrary, the Table Queen cultivar was highly susceptible as evidenced by a rapid expansion of water-soaked lesions to the cotyledons and subsequent wilting and death.…”
Section: Phenotypic Analysismentioning
confidence: 82%
See 1 more Smart Citation
“…However, the presumed quantitative basis of resistance indicates that the other partially resistant accessions likely possess beneficial alleles that may not be present in the PR lines. The resistant accessions identified by Padley et al (2008) have since been genotyped with simple sequence repeat markers and revealed to be genetically like cultivars representing zucchini and pumpkin morphotypes (Michael et al, 2019). The resistance levels of the PR lines could potentially be improved by the incorporation of additional beneficial alleles from these accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical control strategies are difficult to adopt, due to the limited number of registered chemicals that are permitted and the scalar harvest system (Gilardi et al, 2015). However, many efforts have been made to find a source of genetic resistance in squash accessions to PHC strains (Michael et al, 2019;Siddique et al, 2019), but this approach is still at its beginning. For these reasons, alternative PHC control agents are being studied and adopted in agriculture.…”
mentioning
confidence: 99%